2003
DOI: 10.1034/j.1600-051x.2003.00052.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of subgingival calculus removal with Er:YAG laser compared to mechanical debridement: an in situ study

Abstract: The present investigation could demonstrate the in vivo capability of the Er:YAG laser to remove calculus from periodontally involved root surfaces, although the effectiveness did not reach that achieved by hand instrumentation. The lack of cementum removal in contrast to SRP may qualify the laser as an alternative approach during supportive periodontal therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
107
1
11

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(134 citation statements)
references
References 54 publications
12
107
1
11
Order By: Relevance
“…4,7 The surfaces irradiated with Er:YAG and Er,Cr:YSGG lasers showed similar morphological characteristics, including root surface roughness, no smear layer, open dentinal tubules and lack of thermal damage. These characteristics are consistent with those observed in other in vitro studies that evaluated the morphology of dentin irradiated with Er:YAG 4,8,11 and Er,Cr:YSGG lasers. 7,9,12,13 The morphological characteristics of the surfaces irradiated with these lasers are explained by the laser tissue ablation mechanism, called photomechanical ab- …”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…4,7 The surfaces irradiated with Er:YAG and Er,Cr:YSGG lasers showed similar morphological characteristics, including root surface roughness, no smear layer, open dentinal tubules and lack of thermal damage. These characteristics are consistent with those observed in other in vitro studies that evaluated the morphology of dentin irradiated with Er:YAG 4,8,11 and Er,Cr:YSGG lasers. 7,9,12,13 The morphological characteristics of the surfaces irradiated with these lasers are explained by the laser tissue ablation mechanism, called photomechanical ab- …”
Section: Discussionsupporting
confidence: 80%
“…Some studies have shown that irradiation of root surfaces using Er:YAG lasers does not promote the formation of a smear layer. 4,7 Additionally, the Er:YAG and ErCr: YSGG lasers promote a selective removal of calculus with minimal damage to root surfaces, [8][9][10] and may be clinically effective for stabilizing the clinical parameters of periodontal disease. 2,3 Although the Er:YAG 1 and Er,Cr:YSGG 3 lasers have been recommended for root instrumentation, to our knowledge there are no studies reporting a direct comparison between these tools.…”
Section: Introductionmentioning
confidence: 99%
“…20 When irradiation is applied in the subgingival region, which is not in direct contact with the oral environment, this roughness may benefit healing processes because rough surfaces can increase the adhesion of blood components 15 and fibroblasts from the periodontal ligaments. 25 However, it should be taken into consideration that after periodontal treatment, the root surfaces that were once located below the gingival margin will eventually become located above the gingival margin due the retraction of the inflamed gingiva 26 This pattern has been demonstrated in previous studies that compared the roughness of surfaces irradiated with an Er,Cr:YSGG laser 15 or an Er:YAG laser 8 with hand scaling. The rougher texture on root surfaces irradiated with an Er,Cr:YSGG laser may be a result of its thermomechanical ablation mechanism, in which the abrupt evaporation of water from the interprismatic substance promotes micro-explosions that remove hydroxyapatite crystals.…”
Section: Discussionmentioning
confidence: 99%
“…3 Some alternative tools to facilitate SRP have been proposed, such as sonic instruments, 4 ultrasonic instruments 5 and lasers. 6 The alternative use of lasers has been proposed due to some advantages, such as hemostasis, 7 selective calculus removal 8 and antibacterial effects. 9 However, different types of radiation can lead to harmful thermal effects on the root surface 10,11 and can also promote a rough root surface.…”
Section: Introductionmentioning
confidence: 99%
“…1 Unintentional damage can easily occur using hand instruments 6 and power-driven scalers (e.g., ultrasonic and air-abrasion) 7 causing grooves and/or excessive cementum removal. In addition, mechanical root scaling usually leaves behind a smear layer containing harmful bacteria, infected cementum, and calculus debris.…”
Section: Introductionmentioning
confidence: 99%